Evaluation of 3,4-dimethylpyrazole phosphate as a nitrification inhibitor in a Citrus-cultivated soil - Serna, María D.; Banuls, Josefina; Quinones, Ana; Primo-Millo, Eduardo; Legaz, Francisco (2017)
The objectives of this work were to evaluate the inhibitory action on nitrification of 3,4-dimethylpyrazole phosphate (DMPP) added to ammonium sulphate nitrate [(NH4)(2)SO4 plus NH4NO3; ASN] in a Citrus-cultivated soil, and to study its effect on N uptake. In a greenhouse experiment, 2 g N as ASN either with or without 0.015 g DMPP (1% DMPP relative to NH4+-N) was applied 6 times at 20-day intervals to plants grown in 14-l pots filled with soil. Addition of DMPP to ASN resulted in higher levels of NH4+-N and lower levels of NO3--N in the soil during the whole experimental period. The NO3--N concentration in drainage water was lower in the ASN plus DMPP (ASN + DMPP)-treated pots. Also, DMPP supplementation resulted in greater uptake of the fertilizer-N by citrus plants. In another experiment, 100 g N as ASN, either with or without 0.75 g DMPP (1% DMPP relative to NH4+-N) was applied to 6-year-old citrus plants grown individually outdoors in containers. Concentrations of NH4+-N and NO3--N at different soil depths and N distribution in the soil profile after consecutive flood irrigations were monitored. In the ASN-amended soil, nitrification was faster, whereas the addition of the inhibitor led to the maintenance of relatively high levels of NH4+-N and NO3--N in soil for longer than when ASN was added alone. At the end of the experiment (120 days) 68.5% and 53.1% of the applied N was leached below 0.60 m in the ASN and ASN + DMPP treatments, respectively. Also, leaf N levels were higher in plants fertilized with ASN+DMPP. Collectively, these results indicate that the DMPP nitrification inhibitor improved N fertilizer efficiency and reduced NO3- leaching losses by retaining the applied N in the ammoniacal form.